Utilization of the integrated online village and urban village information system in Kendal Regency “Dokar “ as an actievement of bureaucratic reform - Ariningsih, Siti (Green Governance: Exploring Politics, Social Justice, and the Environment, 2024)
Background: Bureaucratic reform that focuses on transparency and public accountability has encouraged the application of information technology in government, particularly through the concept of E-Government. This technology has become an important tool to improve public information disclosure, which is a citizen's right and an important element in participatory decision-making processes. Methods: This research uses a literature study approach with descriptive analysis of various literature and policy documents related to the implementation of village information systems. Data were collected from credible sources, analysed systematically, and presented in narrative form to identify the impact of village information system implementation on public information disclosure. Findings: The results show that the implementation of village information systems, such as the one implemented through DOKAR in Kendal District, significantly improves the accessibility and transparency of public information. The system allows citizens to access information anytime and anywhere, without being limited by time and distance, thus supporting community involvement in supervision and decision-making. Conclusion: The implementation of E-Government through village information systems has opened up new opportunities for public information disclosure, which in turn improves government accountability and community participation. This research confirms the importance of developing and maintaining integrated information systems to support sustainable bureaucratic reform. Novelty/Originality of This Study: This study makes an original contribution by highlighting the specific impact of village information system implementation on public information disclosure at the local level. The analysis enriches the literature on E-Government by providing empirical evidence of the application of information technology in local government, which is rarely addressed in previous studies.